A Patentability Requirement For Sequential Innovation - Ted O'Donoghue (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1997)
This paper investigates patent protection when there is a long sequence of innovations and firms repeatedly supersede each other. There can be insufficient incentives for R&D if successful firms earn market profit only until competitors achieve something better. To solve this problem, patents must provide protection against future innovators. This paper proposes using a patentability requirement aminimuminnovation size required to get a patent toserve this purpose. I showthat a patentability requirement can stimulate R&D investment and increase dynamic efficiency. Intuitively, requiring firms to pursue larger innovations can prolong market incumbency because larger innovations are harder to achieve. Longer market incumbency then implies an increased reward to innovation, stimulating R&D investment.
Keywords: 330